2015
DOI: 10.1371/journal.pone.0139336
|View full text |Cite
|
Sign up to set email alerts
|

Scabies and Bacterial Superinfection among American Samoan Children, 2011–2012

Abstract: BackgroundScabies, a highly pruritic and contagious mite infestation of the skin, is endemic among tropical regions and causes a substantial proportion of skin disease among lower-income countries. Delayed treatment can lead to bacterial superinfection, and treatment of close contacts is necessary to prevent reinfestation. We describe scabies incidence and superinfection among children in American Samoa (AS) to support scabies control recommendations.Methodology/Principal FindingsWe reviewed 2011–2012 pharmacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
1
16
0
3
Order By: Relevance
“…On the whole, scabies ranged from 14.3 to 20% . In American Samoan children with scabies, 53% of them had a bacterial superinfection . In the Solomon Islands, 41.1% of patients with impetigo also had scabies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the whole, scabies ranged from 14.3 to 20% . In American Samoan children with scabies, 53% of them had a bacterial superinfection . In the Solomon Islands, 41.1% of patients with impetigo also had scabies .…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In American Samoan children with scabies, 53% of them had a bacterial superinfection. 11 In the Solomon Islands, 41.1% of patients with impetigo also had scabies. 13 The close relationship between scabies and skin bacterial colonizations and superinfections was demonstrated by two studies which were performed in an Australian Aboriginal community 6 and the Solomon Islands, 12 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Scabies, as well as bacterial skin infections are associated with poverty, overpopulation, poor sanitary conditions, lack of hygiene and malnourishment (7,18). In a study carried out by Edison et al among 1139 in American Samoa, secondary bacterial infection was observed in 604 (53%) patients with scabies (19). In a study conducted by Esposito and Veraldi among 89 patients with scabies only 5 (5.6%) patients had positive bacterial culture from skin lesions (18).…”
Section: Julia Nowowiejska Monika Emilia Król I Innimentioning
confidence: 99%
“…W badaniu przeprowadzonym przez Edison i wsp. wśród 1139 dzieci na terenach Amerykańskich Wysp Samoa wtórne zakażenie bakteryjne opisano aż u 604 (53%) pacjentów ze świerzbem (19). W badaniu przeprowadzonym we Włoszech przez Esposito i Veraldi wśród 89 pacjentów ze świerzbem, jedynie u 5 (5,6%) pacjentów otrzymano dodatnie wyniki posiewów bakteryjnych (18).…”
Section: Julia Nowowiejska Monika Emilia Król I Inniunclassified
“…Permethrin is almost exclusively used for the treatment of scabies, and one study from the Pacific region (American Samoa) has shown high levels of agreement in the number of children with a permethrin prescription and with a scabies diagnosis . To explore whether scabies and ARF are correlated, we examined the spatial relationship between permethrin dispensing as an indicator of scabies prevalence and cases of ARF in Auckland.…”
mentioning
confidence: 99%